ACCREDITATION AS A QUALITY ASSURANCE INSTRUMENT IN EDUCATIONAL INSTITUTIONS - Rochmatunnisa; Evarianty Masfini; Husnul Yaqin; Hilmi Mizani (INJOSEDU: International Journal of Social and Education, 2026)
School/madrasah accreditation is one of the key instruments in Indonesia’s education quality assurance system. This study aims to analyze school/madrasah accreditation policies within the national education quality assurance system, identify the principles underlying their implementation, and describe the role of educational institutions in the accreditation process. This research employs a literature review method by examining various regulations, scientific journals, and relevant policy documents. The findings indicate that accreditation policies in Indonesia have a strong legal foundation, ranging from Law No. 20 of 2003 to the latest IASP 2020 instrument. The implementation of accreditation is based on the principles of objectivity, comprehensiveness, fairness, transparency, accountability, professionalism, as well as meaningfulness, inclusivity, and contextuality. Educational institutions play an active and strategic role in the accreditation process, ranging from self-preparation and the conduct of site visits to follow-up on accreditation results as part of continuous quality improvement efforts. Accreditation is not merely an administrative process but serves as a means for reflection and comprehensive improvement of educational quality.